When dark deeds come to light: Countering negative gender/power tropes from Bible to boardroom - Miles-Tribble, Valerie (Review and expositor, 2021)
Gender bias in leadership is an egregious yet common reality in the societal mores of male-dominant cultures. Contentious ecclesial debates about gender bias pit prejudices against female leadership roles when girded by biblical tropes engaged to disparage female character and leadership behavior. Sexualized imagery in the textual narrative is misappropriated to libel females who are leading change with ethical and behavioral competencies lauded in their male counterparts. In the politically charged context of recent national elections, the newly installed Vice President of the United States was publicly labeled a “Jezebel” to connote a racially and sexually derisive trope calling into question a woman’s scruples in private spheres as well as disparaging her agency. As I refer to Tamura Lomax’s extensive analysis of this trope, I examine in this article the hermeneutical misappropriation of Bathsheba imagery, wherein the behavior of biblical figure King David is normalized as the beloved of God while Bathsheba is villainized. The presumptive insinuation is that women use sexual guiles to advance careers, social station, or positional power. Judgmental inequities in contemporary and biblical examples raise an urgency to counter negative gender/power tropes from the Bible to the boardroom.